2013
DOI: 10.3389/fncir.2013.00166
|View full text |Cite
|
Sign up to set email alerts
|

Neural representation in the auditory midbrain of the envelope of vocalizations based on a peripheral ear model

Abstract: The auditory midbrain implant (AMI) consists of a single shank array (20 sites) for stimulation along the tonotopic axis of the central nucleus of the inferior colliculus (ICC) and has been safely implanted in deaf patients who cannot benefit from a cochlear implant (CI). The AMI improves lip-reading abilities and environmental awareness in the implanted patients. However, the AMI cannot achieve the high levels of speech perception possible with the CI. It appears the AMI can transmit sufficient spectral cues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 80 publications
0
23
0
Order By: Relevance
“…The dataset used in this study consists of multi-unit neural recordings from the inferior colliculus of ketamineanesthetized guinea pigs; the detailed experimental setup can be found in [13]. Recordings were performed simultaneously at 32 different sites following the successive presentation of 6 different guinea pig vocalizations, having both voiced and unvoiced characteristics, for 20 trials each ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The dataset used in this study consists of multi-unit neural recordings from the inferior colliculus of ketamineanesthetized guinea pigs; the detailed experimental setup can be found in [13]. Recordings were performed simultaneously at 32 different sites following the successive presentation of 6 different guinea pig vocalizations, having both voiced and unvoiced characteristics, for 20 trials each ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that ICC neurons can follow envelope modulations of simple and natural stimuli up to a few hundred hertz (Krishna et al, 2000; Langner et al, 2002; Rees et al, 1987; Suta et al, 2003; Woolley et al, 2006). One particular study performed experiments in 10 ketamine-anesthetized guinea pigs to further assess if a CI type of strategy could potentially be effective for the AMI (Rode et al, 2013). Natural vocalizations (i.e., guinea pig speech; Figure 7), which exhibit similar temporal and spectral patterns to human speech, were presented to the left ear of the animals and neural spiking activity was recorded across the right ICC using 32-site arrays in multiple locations per animal.…”
Section: Animal and Human Studies Towards A Second Clinical Trialmentioning
confidence: 99%
“…There were multiple neurons that exhibited high correlation values close to 1 for all three vocalizations, and thus for a wide range of spectral and temporal sound patterns. Based on visual inspection of all the raw data, R values ≥0.85 corresponded to neurons that accurately followed the stimulus envelope (for further examples and justifications of this criterion, see (Rode et al, 2013)). The high 0.85 criterion was achieved by 15%, 60%, and 58% of neurons for scream, squeal, and tooth-chatter, respectively.…”
Section: Animal and Human Studies Towards A Second Clinical Trialmentioning
confidence: 99%
See 2 more Smart Citations